2011
DOI: 10.1016/j.theriogenology.2011.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of the population of preantral follicles in the ovaries of Bos taurus indicus and Bos taurus taurus cattle

Abstract: The number of oocytes recovered from Bos taurus indicus females subjected to ovum pick-up averaged two to four times greater compared to Bos taurus taurus females. The objective of the present study was to test the hypothesis that this difference in oocyte yield was due to more preantral follicles in the ovaries of Bos indicus females. Ovaries (n = 64) from Nelore (Bos indicus) fetuses (n = 10), heifers (n = 12), and cows (n = 10), and Aberdeen Angus (Bos taurus) fetuses (n = 10), heifers (n = 12), and cows (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 41 publications
4
48
0
4
Order By: Relevance
“…Although we did not directly compare cattle and buffalo ovaries, the number of follicles isolated in this study at 3 to 7 months of fetal age was similar to that previously reported in cattle [19], but higher than in buffalo fetuses of the same age [34]. Conversely, the results obtained in regard to in situ follicular quantification in this study were similar not only to those previously reported for Bos indicus [23], but also to buffalo [22] fetuses. Moreover, in agreement with previous studies, there was large variation in follicle population among animals of the same age and among various fetal ages [3,19,20].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although we did not directly compare cattle and buffalo ovaries, the number of follicles isolated in this study at 3 to 7 months of fetal age was similar to that previously reported in cattle [19], but higher than in buffalo fetuses of the same age [34]. Conversely, the results obtained in regard to in situ follicular quantification in this study were similar not only to those previously reported for Bos indicus [23], but also to buffalo [22] fetuses. Moreover, in agreement with previous studies, there was large variation in follicle population among animals of the same age and among various fetal ages [3,19,20].…”
Section: Discussionsupporting
confidence: 89%
“…In the adult bovine ovary, TUNEL and caspase assays have also been used to demonstrate the role of apoptosis in follicles undergoing atresia [18]. Although the ovarian follicular population has been described [19][20][21][22][23], the incidence of apoptosis in the bovine fetal ovary has apparently not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The ovaries were dehydrated in increasing concentrations of alcohol, diaphonized in xylol, embedded in paraffin, and serially sectioned at 5 mm [17] with a rotating microtome (Leica RM2255; Leica Biosystems Melbourne Pty Ltd., Wetzlar, Germany). In all ovaries, one of each 70 histologic sections was mounted and stained with periodic acid-Schiff and hematoxylin [18]. All procedures were performed by the same operator.…”
Section: Histologic Processingmentioning
confidence: 99%
“…This reproducibility of AFC in the same individual becomes a strategic resource for classifying an animal by the AFC with a single ultrasound examination. For taurus animals, AFC is directly correlated with the size of the ovarian follicular reserve (Ireland et al, 2011), which was not proven in indicus females when examining fetuses, heifers, and cows (Silva- Santos et al, 2011). However, other factors, such as genetics (Walsh et al, 2014), maternal environment, nutritional status, and healthiness (Ireland et al, 2011;Evans et al, 2012) also appear to influence the AFC.…”
Section: Introductionmentioning
confidence: 99%